High expression of SOX10 is correlated with poor prognosis and immune infiltrates in skin cutaneous melanoma - Sun, Xu; Cheng, Yi-ming; Sun, Meng-wei; Zhang, Xu-dong; Yu, Xiao-yu; Wang, Hai-bo; Wang, Yi-fei; Li, Ning (Frontiers in Oncology, 2025)
BackgroundSkin Cutaneous Melanoma (SKCM) is a malignant tumor and the prediction of its prognosis remains challenging. Sex determining region Y-box 10 (SOX10) is over-expressed in SKCM and reported to accelerate tumor invasion and immunosuppression. Although studies have suggested the correlation of immune infiltration between SOX10 and SKCM, further in-depth explore of the immunomodulatory role of SOX10 is still needed. Therefore, we assessed the prognostic role of SOX10 and its correlation with immune infiltration and checkpoint expression.MethodsRNA sequencing data were obtained for analysis of SOX10 expression and differentially expressed genes (DEGs) from the Cancer Genome Atlas (TCGA). Moreover, functional enrichment analysis of SOX10-related DEGs was performed by GO/KEGG, GSEA. Receiver operating characteristic (ROC) curves were used to assess the diagnostic value of SOX10 in SKCM. Kaplan-Meier method was conducted to assess the effect of SOX10 on survival. Additionally, the clinical significance of SOX10 in SKCM was figured out by LASSO and prognostic nomogram model. We analyzed SOX10-related immune cell infiltration and expression of immune checkpoints. Finally, validations were performed through immunohistochemical analysis.ResultsSOX10 was low expressed in a range of malignant tumor tissues except SKCM. Totally, 1029 differentially significant genes (DSGs) were identified between SOX10 low- and high- expression group, of which 50 genes were upregulated and 979 genes were downregulated. Additionally, SOX10 high expression was remarkably associated with pathologic stage, age and breslow depth in a sample of 472 cases (P < 0.05). Screening was performed by LASSO coefficients to select non-zero variables that satisfied the coefficients of lambda, and 8 genes were screened out. The forest plot results showed that only OCA2 and TRAT1 had statistical significance (P < 0.05) by multi-factor COX regression analysis. SOX10, OCA2, TRAT1, pathologic stage, age and breslow depth were included in the nomogram prognostic model. Furthermore, upregulation of SOX10 expression inhibited immune infiltration in SKCM.ConclusionOverall, high expression of SOX10 was correlated with poor prognosis in SKCM, which may be related to suppression of immune infiltration. The DSGs and pathways identified in our research have initially provided an insight into the molecular mechanisms underlying the progression of SKCM.